ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF PSEUDOMONAS AERUGINOSA FROM VARIOUS CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL OF RAJASTHAN - Biraj Louriyam; Dr. Ankit Pradhan; Dr. Rakesh K Maheshwari (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction Pseudomonas aeruginosa is a gram-negative, opportunistic pathogen commonly associated with hospital-acquired infections. Due to its intrinsic and acquired resistance mechanisms, it poses significant treatment challenges. Aim and objectives: This study examines the prevalence and antimicrobial susceptibility pattern of P. aeruginosa isolated from various clinical samples in a tertiary care hospital in Rajasthan. Result: A total of 114 isolates were analyzed, revealing a higher prevalence in males (76%) and individuals aged 60-70 years (22%). Blood samples were the most common source (45%), followed by sputum (19%) and body fluids (15%). The most effective antibiotics were Colistin (97%), Tobramycin (87%), and Cefepime (84%), whereas resistance was highest against Tigecycline (71%), Minocycline (68%), and Imipenem (54%).Conclusion: These findings emphasize the need for routine antimicrobial susceptibility testing to guide appropriate treatment and mitigate the spread of multidrug-resistant (MDR) strains.